An investigation of homogeneous electrocatalytic mechanism between ferrocene derivatives and l-cysteine/N-Acetyl-l-cysteine. (20th June 2020) - Yin, Shuang; Song, Peng; Wang, Hao; Ma, Haoyu; Wang, Zhan; Yu, Yanmin
Abstract: The homogeneous electrocatalytic mechanism with a fast catalytic chemical reaction between a series of ferrocene derivatives and l -cysteine/N-Acetyl-l -cysteine (NAC) is systematically investigated. A comparison of different cyclic voltammetric waveforms is given to illustrate the interaction between kinetic parameter (λ) and excess factor (γ) in kinetic zone diagram via changing the scan rates and substrate/mediator ratio on both glassy carbon (GC) and boron doped diamond (BDD) working electrode experimentally. A split wave phenomenon is observed between ferroceneacetic acid (FAA) and l -cysteine. Also, the waveforms revealed that electron withdrawing groups (EWG) on the substrate hinders the kinetics of the homogeneous electron transfer while those on the mediator facilitates the same process. The homogeneous electrocatalytic order of the studied mediator is as follows: 1, 1′-ferrocenedicarboxylic acid (FDA) > FAA > hydroxymethylferrocene (HMF) > 1-hydroxyethylferrocene (HEF) and the corresponding density functional theory (DFT) calculation is applied to support this statement. Furthermore, the second-order rate constant between FAA and l -cysteine is given by the support of numerical simulation (175 (mol m −3 ) −1  s −1 ). The present study would facilitate the understanding of homogeneous electrocatalytic process, especially those possessing a fast catalytic chemical step. Highlights: Experimental voltammetric waveforms of ferrocene derivatives are investigated via kinetic parameter and excess factor. EWGs on substrate and mediator would hinder and facilitate the homogeneous electron transfer kinetics, respectively. A second-order rate constant of 175 (mol m −3 ) −1  s −1 between ferroceneacetic acid and l -cysteine is given via simulation.